Uso dos espaços não-formais na educação básica: o Jardim Botânico da UFSM - Sá, Rithiele Facco de (2018)
The education that is made in formal study places (schools) it’s not enough to the complete development of young citizens. There are no doubts about the importance of Non-Formal Spaces (NFS) to the development of the individual, once they allow the exploration of cultural, social and learning experiences that can’t occur in schools, while it serves too as a complement to expositive classes. In spite of that, for a long time the possibilities created by this NFS have been underestimated. With that perspective, it was realized this masters reseach in the Federal University of Santa Maria (UFSM). The aim is to analyze what are the goals of Basic Education schools when they use NFS. UFSM has several spaces that can be considered Non-Formal, such as Museums and Centers for Research Support that are open to public visitation. Through bibliographical research and documents, we counted ten NFS institutionalized by UFSM. The spaces were grouped, as well as the descriptions generated by information found in documents, texts and official files. We emphasize the Botanical Garden (BG). We selected teachers to be interviewed. For this, it was necessary that each school visited the place as least two times in one year. We opted for the BG, since it has great a great visibility outside of the academic mean, and because of that, it was structured a control tool for the visitations that allowed the selection of schools. We realized that the main goal presented by the teachers is to get outside of the school; stimulate the curiosity of the students, and improve the interaction between teacherstudent. We observed also a much higher frequency of visitations from elementary school; most of teachers do not use the space in its totality, leaving the potential of the BG to be underused. We hope that this research may help to increase the visibility of Non-Formal Spaces in the city of Santa Maria and its surroundings.